Effectiveness Program Modification Behavior In Reducing Anxiety Symptoms In Trypophobia Sufferers - Ambarita, Togi Fitri A; Tambunan, Elsa; Zai, Ribka Rahayu (Jurnal Mamangan, 2023)
This research is experimental research using the A-B-A quasi-experimental single-case design method, carried out on a 19-year-old woman with complaints of fear and disgust at seeing objects/body parts with hollow patterns, or what is called trypophobia. The research aims to reduce the anxiety level of trypophobia sufferers when watching videos that display objects/bodies with a pattern of holes lasting 5 minutes. First, a behavior modification program is prepared before treatment is carried out and agreed upon with the research subjects. In this behavior modification program, new behavior is formed using two main techniques, namely exposure techniques and economic tokens. To measure the level of anxiety, this study used the distress unit scale (SUD) and an anxious behavior observation checklist. Measurements were carried out in three situations, namely baseline, treatment, and follow-up. Treatment is carried out every day with a total of 6 meetings. The SUD results changed from an anxiety level of 80-100 SUD at the baseline stage to 10 SUD after treatment. The results of observations listing changes in anxious behaviour are displayed in graphical form in three situations, which show a decrease in anxious behaviour. A checklist for observing the subject's comfortable behavior throughout the treatment was also carried out. The results showed significant changes in facial expressions and other body language, indicating that the subjects were able to feel more comfortable when watching the video. Thus, the behaviour modification program is effective in reducing the anxiety of trypophobia sufferers and is successful in forming new behaviour, namely from anxious behaviour to calmer/comfortable behaviour.